Analisis Aktivitas Antioksidan, Total Senyawa Fenolik Dan Kandungan Cemaran Aflatoksin Pada Tempe Dari Berbagai Varietas Kedelai (Glycine Max L. Merill) - Wulan Cahyaning Ayu (BiSTeK Pertanian, 2025)
Tempe is an authentic Indonesian fermented product made from soybeans or other types of beans that use the fungus Rhizopus oligosporus and uses the fungus Rhizopus oryzae. Soybean (Glycine max) is one of the sources of vegetable protein, which is relatively cheap compared to animal protein sources. Soybeans contain phenolic compounds. Phenolic compounds contained in soybeans partly act as antioxidants. Soybeans also contain aflatoxin. Tempe made from fermented soybeans can be indicated aflatoxin. In this study using a Complete Random Design (CRD) with four varieties treatment and that is import soybeans "Bola" (A1), local soybean varieties Dena 1 (A2), local soybean varieties Devon 1 (A3) and local soybean varieties Anjasmara (A4).